SUMMARY REQUIRING REGARDLESS OF CREATION DECISION SUPPORT SYSTEM FOR THE DISTRIBUTION CAPABILITIES TO PROVIDE SUFFICIENT EFFICIENCY OF BORDER REGION OF SYSTEMS FOR OPTO-ELECTRONIC SURVEILLANCE (Computer systems and information technologies, 2020)
The article is devoted to the substantiation of the choice of the basic methodology for assessing the effectiveness of the optoelectronic surveillance system, which could be taken as the basic model of this system for the distribution of forces and means to ensure a sufficient level of border protection efficiency. taking into account in the specified basic methodology for assessing the effectiveness of the system. As a result of the study it was found that as a basic method of assessing the effectiveness of the optoelectronic surveillance system, it is advisable to adopt a method based on a probabilistic approach to describe the processes that accompany the functioning of the optoelectronic surveillance system. It is also substantiated that the main provisions that need to be taken into account when creating a decision support system forthe distribution of forces and means to ensure a sufficient level of border protection in the field of optoelectronic surveillance are: homogeneous in terms of features of technical means of border protection time periods; adequate integrated laws of distribution of time periods, which determine the probability of non-detection of the target to its approach to a given distance by certain technical means of border protection, which are part of the studied system of optoelectronic surveillance; points of "stitching" of various integral laws of distribution at the ends of the specified periods; the impact of weather changes over a period of time, which characterizes the period of the service organization, on the functioning of the system; "Dead" zones, which are dynamically variable depending on the natural and man-made conditions that arise in the area of responsibility.
Keywords: decision support system; efficiency; system of optoelectronic observation; technical means of protection; natural conditions; technogenic conditions